Intranasal influenza virus-vectored vaccine offers protection against clade 2.3.4.4b H5N1 infection in small animal models - Ying Liu; Shaofeng Deng; Shuang Ren; Rachel Chun-Yee Tam; Siwen Liu; Anna Jinxia Zhang; Kelvin Kai-Wang To; Kwok-Yung Yuen; Honglin Chen; Pui Wang (Nature Communications)
Abstract The highly pathogenic avian influenza (HPAI) H5N1 virus has been endemic in aquatic birds since 1997, causing outbreaks in domestic poultry and occasional human infections worldwide. Recently, the cross-species transmission of a new reassortant variant from clade 2.3.4.4b of H5N1 to cattle in the US has heightened concerns regarding the expansion of host range and potential human infection. As eradicating the H5N1 virus from its reservoir is impossible, it is essential to prepare for a potential pandemic caused by an H5N1 derivative. Utilizing a deleted-NS1 live attenuated influenza viral vector vaccine system (DelNS1 LAIV), a system we have previously used in the development of a COVID-19 vaccine, we have rapidly developed an intranasal vaccine for cattle H5N1 and related clade 2.3.4.4b strains, based on publicly available sequences. Our research demonstrates that a single intranasal immunization can provide effective protection against lethal challenges from HPAI cattle or mink H5N1 variants, offering strong, sustained immunity after two months in female mouse and male hamster models. Immunogenicity analysis reveals that intranasal vaccination with DelNS1 LAIV induces robust neutralizing antibody, mucosal IgA and T cell responses in mice. It is crucial to further evaluate the DelNS1-H5N1 LAIV system to prepare for potential future H5N1 outbreaks in humans.